Facemasks Block Lower Visual Field in Youth Ice Hockey - Kyle Critelli; Victoria Demiris; Brooke N. Klatt; Benjamin Crane; Benjamin Crane; Benjamin Crane; Eric R. Anson; Eric R. Anson; Eric R. Anson (Frontiers Media S.A., 2021)
Wearing a facemask (FM) reduces the spread of COVID-19, but it also blocks a person's lower visual field. Many new public safety rules were created in response to COVID-19, including mandated FM wearing in some youth sports like youth ice hockey. We hypothesized that FM wearing in youth hockey players obstructs the lower field of view and may impact safety. Youth hockey players (n = 33) aged 12.03 (1.6) years button press when they saw an LED on the floor turn on in two conditions (wearing FM or no FM) in random order. An interleaved one-up/one-down two-alternative-forced-choice adaptive staircase design was used. Visual thresholds were calculated for each condition and participant. The visual angle threshold (VAT) was determined using standing eye height and the linear distance from the tip of the skates to the visual threshold. Paired t-tests determined whether mask wearing changed the VAT. We modeled the probability a player could see the puck on their stick in four distinct scenarios to estimate the potential impact of FM wearing during hockey play. The average unmasked VAT (11.4 degrees) was significantly closer to the skates than the masked VAT (20.3 degrees) (p < 0.001). Our model indicated a significant reduction in ability to visualize the puck using peripheral vision when more upright while wearing a FM. FM wearing compromised their lower visual field, suggesting a downward head tilt may be necessary to see the puck. Playing ice hockey while wearing a FM may lead to unsafe on-ice playing conditions due to downward head tilt to see the puck.